2019
DOI: 10.1002/adts.201800191
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of DNA Replication and Repair Machinery: Insights from Microscopic Simulations

Abstract: Reproduction, the hallmark of biological activity, requires making an accurate copy of the genetic material to allow the progeny to inherit parental traits. In all living cells, the process of DNA replication is carried out by a concerted action of multiple protein species forming a loose protein-nucleic acid complex, the replisome. Proofreading and error correction generally accompany replication but also occur independently, safeguarding genetic information through all phases of the cell cycle. Advances in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 282 publications
(282 reference statements)
0
8
0
Order By: Relevance
“…Rather than examining the absolute rates, such simulations could be used to compare the exchange rates, for example, probing how the exchange rate depends on the length of the ssDNA or perhaps on modifications of the SSB structure. Our simulation approach could be generalized to model competitive binding of SSB and other DNA-binding proteins, such as RecA, to the same DNA fragment, providing insights into the microscopic mechanisms of DNA repair [31].…”
Section: Exchange Of Ssb Proteins Bound To Ssdnamentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than examining the absolute rates, such simulations could be used to compare the exchange rates, for example, probing how the exchange rate depends on the length of the ssDNA or perhaps on modifications of the SSB structure. Our simulation approach could be generalized to model competitive binding of SSB and other DNA-binding proteins, such as RecA, to the same DNA fragment, providing insights into the microscopic mechanisms of DNA repair [31].…”
Section: Exchange Of Ssb Proteins Bound To Ssdnamentioning
confidence: 99%
“…Among the most popular computational approaches, explicit solvent all-atom MD simulations have been applied widely to study the molecular mechanisms underlying biological and biotechnological systems [18,27,21,14,31]. However, the explicit representation of each atom limits routine application of the method to small systems and/or relatively short timescales.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most popular computational approaches, explicit solvent all-atom MD simulations have been applied widely to study the molecular mechanisms underlying biological and biotechnological systems ( Karplus and McCammon, 2002 ; Lindahl and Sansom, 2008 ; Klepeis et al., 2009 ; Hollingsworth and Dror, 2018 ; Maffeo et al., 2019 ). However, the explicit representation of each atom limits routine application of the method to small systems and/or relatively short timescales.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the structural biology techniques, many other experimental techniques including Förster resonance energy transfer (FRET) 13-14 , nuclear magnetic resonance (NMR) 15-16 , mass spectrometry 17-18 , small angle X-ray scattering (SAXS) 19 , electrophoretic mobility shift assay (EMSA) 20-22 , footprinting 20-21 , crosslinking 21, 23 and chromatin immunoprecipitation (ChIP) 20-21, 24-25 focus on proteins-nucleic acids interactions and their dynamics during the biological processes. In addition to these studies, computational approaches based on molecular dynamics (MD) simulations have provided important insights on the dynamics of protein-nucleic acid interactions at the atomistic details 26-32 . MD simulations are used to obtain mechanistic understanding of the roles that protein-nucleic acid interactions play in biological processes 27-28, 32-33 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these studies, computational approaches based on molecular dynamics (MD) simulations have provided important insights on the dynamics of protein-nucleic acid interactions at the atomistic details 26-32 . MD simulations are used to obtain mechanistic understanding of the roles that protein-nucleic acid interactions play in biological processes 27-28, 32-33 . Studies have also shown the importance of force field choice in simulations to reproduce experimental values with high accuracy as they demonstrated that imperfections in the results can occur 29, 34-35 .…”
Section: Introductionmentioning
confidence: 99%